Haematocrit in <35 weeks preterm infants who received at least 60 seconds of delayed cord clamping: a retrospective observational study. Issue 1 (24th September 2019) - Nudelman, Matthew JR; Goel, Keshav; Jegatheesan, Priya; Song, Dongli; Huang, Angela; Govindaswami, Balaji
Abstract : Objective: To describe haematocrit at birth in preterm infants who received ≥60 s of delayed cord clamping (DCC). Design: Retrospective observational study. Setting: A California public hospital with an American Academy of Pediatrics level 4 neonatal intensive care unit, with 3500–4000 deliveries annually. Participants: 467 preterm infants born at <35 weeks' gestational age (GA) between January 2013 and December 2018. Primary and secondary outcome measures: Haematocrit reference ranges for 0–4 hours after birth and paired haematocrit differences between 0–4 and 4–24 hours. Methods: Haematocrits were obtained when clinically indicated and collected from arterial, venous and capillary sources. Haematocrits obtained after packed red blood cell transfusions were excluded. We summarised the first available haematocrit between 0 and 4 hours by GA strata. We used mixed-effects linear regression to describe the associations between haematocrit and predictor variables including GA, male sex and hours after an infant's birth. We also compared paired haematocrits at 0–4 and 4–24 hours after birth. Results: The median GA of the 467 included infants was 33.3 weeks, birth weight was 1910 g and DCC duration was 60 s. The mean (95% CI) first haematocrit at 0–4 hours was 46.6 (45.0% to 48.1%), 51.2 (49.6% to 52.8%), 50.6 (49.1% to 52.1%), 54.3 (52.8% to 55.8%) and 55.6 (54.6% to 56.6%) for infants 23–29, 30–31, 32, 33 and 34 weeks' GA strata, respectively. The subanalysis of 174 infants with paired haematocrits at 0–4 and 4–24 hours showed that for each additional hour after birth, the mean (95% CI) haematocrit increased by 0.2 (0.1% to 0.3%), 0.2 (0.1% to 0.4%) and 0.1 (0.0% to 0.2%) for infants in 23–29, 30–31 and 32 weeks' GA strata, respectively. The subanalysis showed no change between the paired haematocrits in the 33 and 34 weeks' GA strata. Conclusions: Our study describes haematocrit in preterm infants who received ≥60 s DCC as standard of care. Haematocrit during the first 0–4 hours in our study is higher than the previously described reference ranges prior to DCC becoming routine clinical practice. The paired second haematocrit at 4–24 hours is higher than haematocrit at 0–4 hours.